The Role of Gender and Culture in Dealing with the Arab Woman's Issues Embodied in Caricatures: A Cognitive Linguistic Analysis (Journal of the College of Languages (JCL), 2022)
Gender and culture are among the factors that influence the process of understanding and interpreting different types of communication, especially images. The current study, which is a part of a master’s thesis, aims at investigating the role of gender and culture in interpreting and understanding the caricatures that deal with women’s issues in Arab societies. To this end, the researchers adopted Barthes’ (1957) concepts of denotation and connotation in his theory of mythologies in addition to Langacker’s (1987) theory of (Domains). The research concludes that the female subjects have better cognitive abilities in investing the signs within the selected caricatures. The other factor the study reached to is that the respondents’ different cultures didn’t affect their way of dealing with the caricatures very much, so they supported the issues raised in the caricatures almost equally.